A Closer Look at Junior High School English Teachers in Pekanbaru: Does the Reluctance of Teachers to Adapt with ICT Hindering English Learning? - Simangunsong, Wendy (Universitas Lancang Kuning, 2019)
Though English Education has universally acknowledged technology as a fundamental consideration, there exists a gap between the IT skills of teachers and students due to teachers’ reluctance to adapt Internet/information communications technology (ICT) in their English teaching. This paper looked closely at 131 junior high schools in Pekanbaru, Indonesia to ascertain if the conservative teaching mindset may be preventing English learning of students. Mixed method is used to analyze the data collected from 171 English teachers through online and offline questionnaires from a previous study that uncovered 5 key problems of ICT usage in teaching English, namely teachers’ lack of IT knowledge, lack of ICT facilities, lack of self-confidence, lack of much time, and lack of willingness to change their teaching style.